What causes the colossal C supersaturation of δ-ferrite in stainless steel during low-temperature carburization?. (15th March 2019) - Sasidhar, K.N.; Meka, S.R.
Abstract: This study shows for the first time, with the help of thermodynamic calculations, that the colossal carbon supersaturation in delta-ferrite during low temperature carburization of stainless steels is not opposed to the concept of metastable carbon paraequilibration of delta-ferrite with the carburizing atmosphere. Rather, it is a consequence of triggering spinodal decomposition during the process of establishment of carbon paraequilibrium. This kind of paraequilibrium between spinodally decomposed ferrite and carburization atmosphere has not been recognized before. This renewed understanding explains the origin of colossal C supersaturation and also the strong variation in C solubility within a ferrite grain. Graphical abstract: Unlabelled Image